Comparison of Three Alleles at a Major Solid Stem QTL for Wheat Stem Sawfly Resistance and Agronomic Performance in Hexaploid Wheat. Issue 4 (1st July 2019) - Cook, J. P.; Weaver, D. K.; Varella, A. C.; Sherman, J. D.; Hofland, M. L.; Heo, H.‐Y.; Caron, C.; Lamb, P. F.; Blake, N. K.; Talbert, L. E.
ABSTRACT: Solid stems provide resistance to the wheat stem sawfly (WSS, Cephus cinctus Nort.) in wheat ( Triticum aestivum L.). A major quantitative trait locus, designated Qss.msub‐3BL, controls most of the variation for stem solidness. Two alleles that differ for temporal expression of stem solidness have been identified. An allele derived from the cultivar 'Rescue', designated Qss.msub‐3BL.b, results in solid stems throughout stem development. An allele derived from the cultivar 'Conan', designated Qss.msub‐3BL.c, causes high stem solidness early in plant development, but solidness declines as the plant matures. The objective of this study was to develop near‐isogenic lines (NILs) derived from marker‐assisted backcrossing to compare the impact of Qss.msub‐3BL alleles in different genetic backgrounds on stem solidness, WSS resistance, and agronomic traits. The Conan‐derived allele Qss.msub‐3BL.c resulted in lower WSS infestation than the Rescue‐derived allele Qss.msub‐3BL.b in two genetic backgrounds. Both alleles showed a high level of early stem solidness, though this declined as the stem matured for NIL with the Conan‐derived allele. The Conan‐derived allele Qss.msub‐3BL.c resulted in lower WSS infestation and stem cutting than the allele for hollow stems in two genetic backgrounds. Based on yield trials grown over 2 yr, there were no significant differences in grain yield between the NIL pairs. Our results indicate the Conan‐derived allele at Qss.msub‐3BL results in lower infestation of WSS and does not significantly affect agronomic performance, thus providing a novel source of resistance for the development of WSS‐resistant cultivars.